Transfer Pricing for the Multinational Firm. - Merville, Larry J.; Petty, J. William (The Accounting Review, 1978)
Abstract ABSTRACT: There are several aspects of the international business environment which affect the setting of a transfer price. These items include the various methods and rates of income taxation; quotas and duties imposed on imported materials; capital flow restrictions and currency regulations imposed by a host government; and managerial preferences for risk avoidance through consideration of risks associated with foreign exchange rate fluctuations, rates of inflation and nationalization. Also, the behavioral dimension of managerial rewards and controls must be considered in the transfer pricing problem. Since transfer prices usually cannot be set to accomplish all of these goals simultaneously, some means must be devised by which the firm's multiple objectives are optimized, In this vein, the transfer pricing problem is formulated in both a single-objective and a multiple-objective approach for comparison purposes. Specifically, the transfer pricing problem is couched in both a linear programming and a goal programming framework to allow for the optimization of differing tax rates, profit requirements, and exposure and nationalization risks around the world.